The Similarity And Differentiations - Sedlák, Jozef (Communication Today, 2025)
The paper supports the search of space for interpretation of a photographic image in the teaching process and specifies the typical features of the photography medium such as identity, identification of image, fiction in the reality of an image and personal story. The photography can by simultaneously perceived as a technical record of reality, as the production and exchange of the image meaning or as a unique personal story – intention of the author. The main aim of the article is to point to the clarity and ambiguity of the space of photography medium, which are very important to be defined and named in the teaching process. The presented text should be under-stood more like a logical coexistence of connections of described relations of the photography medium within arts, which inevitably interfere in similarities and differences. Sometimes they are even not able to understand each other. Anyway, they make up the basis of photography medium. My intention is the effort for legitimate and more existential thinking about the canon and exceptions emerging from the interpretation of photographic image, which in this case presents the principle of uniqueness and which is characterized by the space of story´s emotion.